USP15 Enhances Re-epithelialization Through Deubiquitinating EIF4A1 During Cutaneous Wound Repair - Zhao, Yixuan; Huang, Xin; Zhang, Zewei; Zhang, Yifan; Zhang, Guoyou; Zan, Tao; Li, Qingfeng (Frontiers in Cell and Developmental Biology, 2020)
Re-epithelialization is a fundamental process in wound healing that involves various cytokines and cells during cutaneous barrier reconstruction. Ubiquitin-specific peptidase 15 (USP15), an important member of the deubiquitinating enzymes (DUBs), removes ubiquitin chains from target proteins and maintains protein stability. However, the dynamic role of USP15 in epithelialization remains unclear. We aimed to investigate the regulatory function of USP15 in re-epithelialization. An excisional wound splinting model was established to evaluate the re-epithelialization rate in Usp15 knockout (KO) mice. Coimmunoprecipitation (Co-IP) and mass spectrum analyses were performed to identify USP15-interacting proteins. RNA-sequencing was performed for transcriptome analysis in keratinocytes and uploaded into NODE database (http://www.biosino.org/node, accession numbers: OEP000770 and OEP000763). First, a significant delay in epithelialization was observed in the Usp15 KO mice. Moreover, inhibition of cell migration and proliferation was observed in the USP15-silenced keratinocytes (HaCaTs). Moreover, we revealed for the first time that USP15 could interact with eukaryotic initiation factor 4A-1 (EIF4A1), thereby promoting translational efficacy in keratinocytes, which is essential for keratinocyte proliferation and migration. Conclusively, the USP15-EIF4A1 complex significantly accelerated re-epithelialization in wound healing. These observations helped elucidate the function and mechanisms of USP15 in modulating re-epithelialization in wound healing, providing a promising target for refractory wound treatment.